Unequal partners : the United States and Mexico - Weintraub, Sidney, 1922-2014 (Pitt Latin American series., 2010)
Over the past 30 years, Mexico has been plagued by debt, currency fluctuations, tax collection problems, political corruption, and state controlled business monopolies that block foreign investment and imports. Weintraub offers changes that would help Mexico level the playing field. Most importantly, he points to developing policies that are proactive. Each chapter also contains a timeline addressing the development of the issues addressed in that chapter.